Considerations Regarding the Optically Transparent Rigid Model for PIV Investigations. A Case Study. Part1: Model Manufacturing. (January 2016) - Nascutiu, Lucian; Giurgea, Corina; Damian, Mihai; Bode, Florin; Budiu, Octavian; Andercou, Octavian
Abstract: The optically transparent model is one of the key components of an experimental set-up dedicated to PIV investigations of internal flows. The accuracy of the PIV results is strongly dependent on the quality of the images captured during the investigation. A prerequisite condition in order to assure the appropriate quality of the PIV images is that of avoiding scattered light, diminishing reflections and refractions of the light. These disturbing phenomena occur especially at the interface between the curved walls and the working fluid. In order to avoid them, the material of the model and the working fluid should comply with the Refractive Index Matching (RIM) condition. This means that they should have, as much as possible, similar or very close values to the refractive indices. Despite the fact that a lot of possible pairs of material-working fluid complying with the RIM condition are presented in literature, the choice is difficult with regard to the possibility of using them effectively in the experimental set-up. Health and safety, the risk of corrosion, availability, technology limitations and fabrication costs should be taken into account. The paper presents the technology the authors designed and used to fabricate rigid transparent models made of Poly(methyl methacrylate) (PMMA). The most important steps followed are briefly described, as well as several tests they conducted in order to assess which testing fluid would be more appropriate for their investigation.